Pengaruh Wakaf Saham Dan Wakaf Produktif Terhadap Pasar Modal Syariah Serta Pertumbuhan Ekonomi Masyarakat - Mohammad Majduddin (MASADIR: Jurnal Hukum Islam, 2023)
This research aims to analyze the direct and indirect effects of stock endowments and productive endowments through the Islamic capital market on economic growth in Indonesia. The analysis method used is path analysis. The results of the research show that, directly, stock endowments have a positive and significant influence on the Islamic capital market, and the Islamic capital market also has a positive and significant influence on economic growth. On the other hand, productive endowments do not have a significant direct influence on the Islamic capital market or economic growth. Indirectly, both stock endowments and productive endowments through the Islamic capital market have a negative and non-significant influence on economic growth. Based on these analysis results, it can be concluded that stock endowments can be used as an instrument to develop the Islamic capital market in Indonesia and contribute positively to economic growth. Meanwhile, productive endowments still do not have a significant influence on the Islamic capital market or economic growth. Therefore, efforts are needed to enhance the effectiveness of productive endowments in driving the Islamic economy in Indonesia